Numerical-experimental analysis of ceramic block masonry walls of different thickness at high temperatures - Bolina, Fabrício; Tutikian, Bernardo; Gonçalves, Jordana; Souza, Thiago; Manica, Gustavo (Revista ALCONPAT, 2019)
The study discusses the fire resistance of vertical sealing systems composed of ceramic bricks with vertical holes at high temperatures. The masonry sealing construction system is widely used in the Brazilian construction market because it is a low cost and high productivity system compared to conventional elements. The results were obtained with finite element computational models, using the Ansys Mechanical software, calibrated by a real scale experimental test, determining the fire resistance time (FRT) for different block geometries. The computational analysis led to results that point to a limit in efficiency of the wall thickness increase in order to reach a high FRT in relation to the thermal insulation.